Two instruments based on differential optical absorption spectroscopy (DOAS) to measure accurate ammonia concentrations in the atmosphere - H. Volten; J. B. Bergwerff; M. Haaima; D. E. Lolkema; A. J. C. Berkhout; G. R. van der Hoff; C. J. M. Potma; R. J. Wichink Kruit; W. A. J. van Pul; D. P. J. Swart (Atmospheric Measurement Techniques, 2012)
We present two Differential Optical Absorption Spectroscopy (DOAS) instruments built at RIVM: the RIVM DOAS and the miniDOAS. Both instruments provide virtually interference-free measurements of NH3 concentrations in the atmosphere, since they measure over an open path, without suffering from inlet problems or interference problems by ammonium aerosols dissociating on tubes or filters. They measure concentrations up to at least 200 μg m−3, have a fast response, low maintenance demands, and a high up-time. The RIVM DOAS has a high accuracy of typically 0.15 μg m−3 for ammonia for 5-min averages and over a total light path of 100 m. The miniDOAS has been developed for application in measurement networks such as the Dutch National Air Quality Monitoring Network (LML). Compared to the RIVM DOAS it has a similar accuracy, but is significantly reduced in size, costs, and handling complexity. The RIVM DOAS and miniDOAS results showed excellent agreement (R2 = 0.996) during a field measurement campaign in Vredepeel, the Netherlands. This measurement site is located in an agricultural area and is characterized by highly variable, but on average high ammonia concentrations in the air. The RIVM-DOAS and miniDOAS results were compared to the results of the AMOR instrument, a continuous-flow wet denuder system, which is currently used in the LML. Averaged over longer time spans of typically a day, the (mini)DOAS and AMOR results agree reasonably well, although an offset of the AMOR values compared to the (mini)DOAS results exists. On short time scales, the (mini)DOAS shows a faster response and does not show the memory effects due to inlet tubing and transport of absorption fluids encountered by the AMOR. Due to its high accuracy, high uptime, low maintenance and its open path, the (mini)DOAS shows a good potential for flux measurements by using two (or more) systems in a gradient set-up and applying the aerodynamic gradient technique.